Supply Chain Management in India: Addressing Challenges, Fostering Innovation, and Achieving Global Competitiveness in a Dynamic Economic Environment - Kulkarni, Soham; Kulkarni, Varun (Journal of Global Economy, Business and Finance, 2025)
India’s supply chain management sector plays a pivotal role in driving the country’s economic growth, especially in light of its expanding global presence in manufacturing, retail, and e - commerce. However, challenges such as infrastructure limitations, regulatory complexities, and inefficiencies in logistics still pose significant obstacles. This paper explores the current landscape of supply chain management in India, focusing on key challenges and the innovations reshaping the sector, including digital transformation, automation, and sustainability initiatives. The paper also examines strategies for improving global competitiveness, addressing regulatory issues, and enhancing collaboration between stakeholders in India’s supply chain ecosystem. Finally, the study outlines the future trajectory of supply chain management in India and its potential to become a global logistics hub.